Temporární hemiepifyzeodéza při korekci osových deformit pro genua valga: retrospektivní zhodnocení a srovnání výsledků při použití osmičkových dlah a Blountových skob - Turek, J; Homolová, N; Urbášek, K; Seehofnerová, A; Plánka, L; Marek, O (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
PURPOSE OF THE STUDY Axial deformities of the lower limbs of various aetiologies are relatively common orthopaedic diagnoses in paediatric population. Fixed deformity is an indication for correction in order to reduce the pain and to delay the early osteoarthrosis of adjacent joints and pain. Temporary hemiepiphysiodesis is technically a fairly simple method for modulating growth at the level of the growth plate and thus correcting the skeletal axis. MATERIAL AND METHODS 59 patients who underwent axial deformity correction of lower limbs at KDCHOT FN Brno were retrospectively analysed. Group 1 consisted of 21 patients with Blount staples implantation, Group 2 consisted of 38 patients to whom eight-figure plates had been applied. Anthropometric parameters (BMI, age, gender, intermalleolar distance (IMD)), duration of therapy, X-ray parameters (anatomical lateral distal femoral angle (aLDFA), anatomical medial proximal tibial angle (aMPTA)) and complications were recorded. The rate of correction was evaluated as the difference in X-ray parameters before and after surgery with respect to the time interval of the therapy. RESULTS The groups were comparable in terms of anthropometric parameters (BMI (p=0.800), IMD (p=0.334), gender (p=0.87)). The only statistically significant difference was found when comparing the mean age of the groups (p=0.005), with Group 1 (12.7±0.7) containing patients with a higher mean age than Group 2 (11.6±1.5). The groups were also comparable in terms of the average rate of correction over a one-month interval (aLDFA p=0.393; aMPTA p=0.831). The mean correction rate for Group 1 was: aLDFA 0.52±0.20/month, aMPTA 0.12±0.08/month; for Group 2: aLDFA 0.56±0.28/month, aMPTA 0.12±0.20/month. Individual implants differed in the type of complications, but no significant statistical difference in the incidence of complications was found between the analysed groups (p=0.526). DISCUSSION Recently, the system of eight-figure plates has been adopted as a standard method for correction of axial deformities of limbs. Although the benefits of this system are indisputable, when comparing the average monthly correction rate, no significant difference was found between the system of eight-figure plates and Blount staples in our study. Another monitored parameter was the occurrence of complications, which was evaluated fairly strictly. Even in this case, no statistically significant difference was found. We believe that the issue of using eight-figure plates is still open, as evidenced by studies, which often produce different results and conclusions. Therefore, a precise evaluation of the indication for correction, including individual characteristics of patients, is needed. CONCLUSIONS Based on the results, it can be concluded that the use of eight-figure plates in comparison with Blount staples provides neither faster correction of axial deformities nor lesser occurrence of complications. It can therefore be argued that the Blount staples still have their place in the indication of correction of axial deformities. The use of eight-figure plates represents a suitable solution for children of younger age to whom anchoring of the screws of eight-figure plates is a suitable solution in the cartilaginous epiphysis of long bones of younger children. Key words: temporary hemiepiphysiodesis, growth plate, Blount staples, eight-figure plates.
Keywords: Pain; tibie; bolest; Child; Bone Plates; lidé; retrospektivní studie; kostní destičky; Tibia; genua valga; dítě; Genu Valgum; Epiphyses; Retrospective Studies; epifýzy; Humans